Dying among older adults in Switzerland: who dies in hospital, who dies in a nursing home? - Luta, Xhyljeta (BMC Palliat Care, 2016)
BACKGROUND: Institutional deaths (hospitals and nursing homes) are an important issue because they are often at odds with patient preference and associated with high healthcare costs. The aim of this study was to examine deaths in institutions and the role of individual, regional, and healthcare supply characteristics in explaining variation across Swiss Hospital Service Areas (HSAs). METHODS: Retrospective study of individuals ≥66 years old who died in a Swiss institution (hospital or nursing homes) in 2010. Using a two-level logistic regression analysis we examined the amount of variation across HSAs adjusting for individual, regional and healthcare supply measures. The outcome was place of death, defined as death in hospital or nursing homes. RESULTS: In 2010, 41,275 individuals ≥66 years old died in a Swiss institution; 54 % in nursing homes and 46 % in hospitals. The probability of dying in hospital decreased with increasing age. The OR was 0.07 (95 % CI: 0.05–0.07) for age 91+ years compared to those 66–70 years. Living in peri-urban areas (OR = 1.06 95 % CI: 1.00–1.11) and French speaking region (OR = 1.43 95 % CI: 1.22–1.65) was associated with higher probability of hospital death. Females had lower probability of death in hospital (OR = 0.54 95 % CI: 0.51–0.56). The density of ambulatory care physicians (OR = 0.81 95 % CI: 0.67–0.97) and nursing homes beds (OR = 0.67 95 % CI: 0.56–0.79) was negatively associated with hospital death. The proportion of dying in hospital varied from 38 % in HSAs with lowest proportion of hospital deaths to 60 % in HSAs with highest proportion of hospital deaths (1.6-fold variation). CONCLUSIONS: We found evidence for variation across regions in Switzerland in dying in hospital versus nursing homes, indicating possible overuse and underuse of end of life (EOL) services. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12904-016-0156-x) contains supplementary material, which is available to authorized users.